2022
DOI: 10.1177/00222437221122994
|View full text |Cite
|
Sign up to set email alerts
|

Intransitivity of Consumer Preferences for Privacy

Abstract: Consumers frequently exchange their private personal data with companies in return for goods and services such as access to search results or social networks. We provide a normative criterion to help assess whether companies adequately compensate consumers for their private data in these exchanges. Across a series of eleven experiments, we find that individuals place a higher price on their private data when they sell them for money than when they barter them for goods. In an application of the compatibility p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Indeed, anonymity is a form of privacy that affords freedom from identification and, to some extent, social expectations (Westin, 1967). Giving publicly (vs. anonymously) therefore entails sacrificing something of value (i.e., one's privacy; Tomaino et al, 2023).…”
Section: Public Donations Drive Inferences Of Egoistic and Altruistic...mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, anonymity is a form of privacy that affords freedom from identification and, to some extent, social expectations (Westin, 1967). Giving publicly (vs. anonymously) therefore entails sacrificing something of value (i.e., one's privacy; Tomaino et al, 2023).…”
Section: Public Donations Drive Inferences Of Egoistic and Altruistic...mentioning
confidence: 99%
“…Indeed, anonymity is a form of privacy that affords freedom from identification and, to some extent, social expectations (Westin, 1967). Giving publicly (vs. anonymously) therefore entails sacrificing something of value (i.e., one's privacy; Tomaino et al, 2023). Because altruism is sometimes defined as a behavior that benefits others at a cost to the person performing it (Fehr & Fischbacher, 2003; West et al, 2011), the presence of this potential cost could contribute to the perception of public donors as altruistically motivated.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Personal information is considered to be a resource or a social commodity (Buckman et al, 2019;Cloarec et al, 2022;Jiang et al, 2013) insofar as it enables firms not only to provide accurate product recommendations and customized content to personalize the consumer's online experience but also to create streams of revenue by selling consumer data to information brokers (Buckman et al, 2019). Studies have shown that consumers demand monetary value in exchange for providing their personal information to firms (Buckman et al, 2019;Tomaino et al, 2022).…”
Section: The Effect Of Consumer Self-disclosure On Promotional Responsementioning
confidence: 99%
“…In other words, providers engage in social exchanges with the expectation of receiving notable benefits from the other party. Therefore, in the case of self-disclosure, consumers regard disclosure behavior as a form of resource exchange (White, 2004), and they are assumed to seek maximum benefits, such as higher-quality service, promotional products, and personalized offers or discounts, given the costs of providing their personal information (Tomaino et al, 2022;Xu et al, 2014). In agreement with this idea, researchers suggested a disclosure-liking effect, which means that disclosure can enhance the discloser's liking of the recipient and significantly affect his or her subsequent behavior.…”
Section: The Effect Of Consumer Self-disclosure On Promotional Responsementioning
confidence: 99%
“…A wealth of literature has examined how choice architecture affects privacy choices (Johnson et al 2002, Acquisti et al 2012, 2013, Adjerid et al 2019, Kormylo & Adjerid 2021, D'Assergio et al 2022, Tomaino et al 2022. Our innovation lies in relating the frame effects to how consumers self-select into sharing data and the quality of data available to firms.…”
Section: Introductionmentioning
confidence: 99%